Pengembangan Bahan Ajar Berbasis Komik pada Pembelajaran Parafrasa Teks Hikayat menjadi Cerpen Siswa Kelas X SMAN 10 Samarinda - Maya Susilawati; M. Jafar Haruna; Bibit Suhatmady (Universitas Mulawarman, 2023)
This study aims to determine (1) the design of comic-based teaching materials; (2) the feasibility of comic-based teaching materials; and (3) the effectiveness of comic-based teaching materials. The scope of this development is limited only to planning, materials, and evaluation in the learning process. The method used in this development research is the R&D (Research and Development) research and development method, which is a type of method used to produce certain products and test the effectiveness of these products. This R&D method uses the Brog and Gall development research design adapted by Sugiyono. The data collection technique used a questionnaire in the form of a questionnaire and a test of the ability to paraphrase the hikayat text into a short story. After the final trial, students' learning completeness in learning to paraphrase the text of a hikayat into a short story was 88.23%. The developed teaching materials were declared very feasible through material expert tests (91.66%), media/design experts stated that they were very feasible (88.88%), and educational practitioners stated that they were very feasible (87.5%). Therefore, comic teaching material in learning to paraphrase hikayat text into short stories can be used as a supporting source in the learning process.